PENERAPAN MODEL PEMBELAJARAN KOOPERATIF LISTENING TEAM UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM DAN BASA DI KELAS XI IPA SMA NEGRI 5 PEKANBARU - Intan Juliana Tombeg Juliana Tombeg; R Usman Rery Rery; Sri Haryati Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievement on the subject Acid and Alkaline solution in class XI IPA SMAN 5 Pekanbaru. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 5 Pekanbaru. The samples of this research were the students of class XI IPA 3 as the experimental class and students of class XI IPA 2 as the control class. Experimental class is a class that is applied learning model listening team, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,3843 > 1,67, means that the application of learning model listening team can improve student achievement on the subject of acid and alkaline solution class XI IPA SMAN 5 Pekanbaru, increase learning of 8,38%. Keywords : Learning Achievement, Learning model listening team, and Acid and alkaline solution